Kierunki działań promocyjnych w zakresie napływu bezpośrednich inwestycji zagranicznych - Kuźmiak, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article contains the directions of the promotion activities in foreign direct investment, the role of the Polish Information and Foreign Investment Agency and the perspective of investment inflow. In conclusion it may be stated that the main objective is intensification of positive image of our country and its economy. According to the last studies foreign investors place their capital in Poland more often. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 185-195